EFFECT OF MASSAGE AND AROMATHERAPY ON STRESS AND PROLACTIN LEVEL AMONG PRIMIPAROUS PUERPERAL MOTHERS IN SEMARANG, CENTRAL JAVA, INDONESIA - Melyana Nurul Widyawati; Soeharyo Hadisaputro; Anies Anies; Ariawan Soejoenoes (Belitung Raya Foundation, Indonesia, 2016)
Background: Exclusive breastfeeding in Semarang during the past five years remains low. Only 20 to 64% of mothers were breastfed exclusively in 2010-2012. The incidence of postpartum blues was reported by 29.9% of mothers and most of them were primiparous. Objective: This study aims to determine the effect of loving massage, aromatherapy, and a combination of loving massage and aromatherapy on stress levels, and changes in levels of prolactin in primiparous puerperal in Semarang. Method: A true experimental study with a randomized pretest-posttest control group design. Cluster random sampling was used to select 12 health centers from the 37 health centers in Semarang. A random assignment with a sealed envelope was performed to divide study participants into four groups; loving massage group, aromatherapy group, and a combination group of loving massage and aromatherapy, and a control group. A total of 52 primiparous puerperal mothers was involved, with 13 mothers were distributed equally in each group. Results: Loving massage, aromatherapy, and a combination of loving massage and aromatherapy effectively changed mother’s stress and prolactin levels. Effectiveness of each treatment assessed from the average difference in scores before and after treatment. Combination of loving massage and aromatherapy had proven as the most effective treatment in reducing stress levels (11.61 ± 6.76), and increasing prolactin level (83.13 ± 6.41 ng/ml). Conclusions: Loving massage and aromatherapy shown to lower the levels of stress, and can increase the levels prolactin in postpartum primiparous. Therefore, it is recommended to provide loving massage therapy and aromatherapy to postpartum primiparous mothers.